An introduction to the study of insects - Borror, Donald J (Holt, Rinehart and Winston, 1976)
This text uses a taxonomic approach to introduce students to the science of entomology. Extensive use of identification keys acquaints students with all the families of insects in the United States and Canada and provides means for students to identify 95% or more of the insects found occurring in North America. --This text refers to an out of print or unavailable edition of this title.